ANTIDEPRESSANT ACTION OF HARMINE HYDROCHLORIDE - Zh. S. Nurmaganbetov; L. I. Arystan; A. Zh. Turmukhambetov; A. A. Anaev; T. A. Voronina; A. K. Sariev; S. M. Adekenov (Фармация и фармакология (Пятигорск))
The articles presents the results of antridepressant action of water-soluble form of harmine hydrochloride.